Ideal profile of educator for adolescents without a valid family support - Baranauskienė, Ingrida; Radzevičienė, Liuda; Grazioli, Porfirio (Social Welfare: Interdisciplinary Approach, 2011)
In many countries the concept of educator has rather wide understanding and interpretation. Presented theoretic Christian issue reveals a profile, as far as possible close to the model of vocational counseling for adolescents without a valid family support. The needs that are common to this group of youngsters have, obviously, totally peculiar characteristics, and in this way could be described as special needs. To these special needs and necessities are added those deriving from the ways of management of living in a community, when this, for example, is based on the pedagogical methods of the so-called self-government.Theory and practice applied in the community of Città dei Ragazzi presents educational action carried out by Msgr. J. P. Carroll-Abbing. The main issue of which is support, assistance and love for youngsters coming from different parts of the world.
Keywords: Christian paradigm of vocational counseling; role of educator; vocational counseling